Carbon Dioxide Leakages through Fault Zones: Potential Implications for the Long-term Integrity of Geological Storage Sites - Duoxing Yang; Lianzhong Zhang (Aerosol and Air Quality Research)
Abstract Carbon sequestration has recently become more widely recognized as a potential means of reducing atmospheric carbon dioxide levels. Understanding the tectonic relationship of carbon dioxide discharges and the sealing behavior of faults is conducive for predicting the long-term integrity of geological storage formations. Of primary concern is the influence of crustal deformation on the carbon dioxide leakage through fault zones during large-scale underground injection. This paper examines a record of carbon dioxide leakage from a faulted, natural carbon-dioxide-rich formation, and investigates the crustal tilt in the fault zones. Temporal changes in the crustal tilt reveal pulses of carbon dioxide concentrations ranging from 537.7 up to 1317.1 ppm, and the mean level represents 890.2 ppm. Of particular interest is that each high-frequency pulse coincides with the onset of local solid-earth tide. We show a significant correlation between the crustal tilt magnitude and amount of carbon dioxide leakage. We suggest that carbon dioxide leakage levels increase owing to fracture opening, potentially caused by changes in fault architecture and permeability structure of regions surrounding the faults.